Under great white northern lights [videorecording (DVD)] - Malloy, Emmett (Warner Bros. Records, 2009)
In 2007 Emmett Malloy joined the White Stripes Canadian tour to record their concerts in venues ranging from concert halls to bowling alleys to fishing boats to tiny town squares.